A pooled analysis of diffusion‐weighted imaging in the diagnosis of hepatocellular carcinoma in chronic liver diseases. Issue 2 (22nd January 2013) - Wu, Lian‐Ming; Xu, Jian‐Rong; Lu, Qing; Hua, Jia; Chen, Jie; Hu, Jiani
Abstract Background and Aim The purpose of this study was to perform a meta‐analysis of all available studies of the diagnostic performance of diffusion‐weighted imaging (DWI) in the detection of hepatocellular carcinoma (HCC) in patients with chronic liver disease. Methods Databases including MEDLINE and EMBASE were searched for relevant original articles published from January 2000 to April 2012. Pooled estimation and subgroup analysis data were obtained by statistical analysis. Results Across the nine studies (476 patients), DWI sensitivity was 81% (95%CI: 67%–90%), and specificity was 89% (95% CI: 76%–95%). Overall, positive likelihood ratio was 7.11 (95%CI: 3.50, 14.48), negative likelihood ratio was 0.21 (95%CI: 0.12–0.37), and the diagnostic odds ratio (DOR) was 33.48 (95%CI: 16.67–67.25). The area under the curve of the summary receiver operator characteristic (ROC) was 0.92 (95% CI:0.89–0.94). In studies in which both DWI and conventional contrast‐enhanced magnetic resonance imaging (CE‐MRI) were performed, the comparison of DWI performance with that of conventional CE‐MRI suggested no major differences against these two methods (P > 0.05). DWI combined CE‐MRI had higher pooled sensitivity than DWI alone (93% vs 73%) (P < 0.05). Conclusion DWI has good diagnostic performance in the detection of HCC in patients with chronic liver disease and equivalent to conventional CE‐MRI. Combination of CE‐MRI and DWI can improve the diagnostic accuracy of MRI. Further larger prospective studies are still needed to establish its value for detecting HCC in patients with chronic liver disease.